Correlation of Age, Administration Method, and Amlodipine Dosage with the Risk of Side Effects in Hypertensive Patients - Tarapanjang, Tiara Rambu Renesia; Riwu, Magdarita; Lada, Christina Olly; Tallo Manafe, Derri Riskiyanti (Cendana Medical Journal, 2024)
Hypertension, known as the "silent killer," poses a global threat with potentially fatal consequences. Lifelong treatment, often involving Amlodipine, requires careful management of age, dosage, and administration to mitigate side effects and enhance patients' quality of life. This study at RSUD Prof. Dr. W. Z. Johannes Kupang aimed to explore the correlation between age, Amlodipine dosage, and side effect risks. Utilizing an observational analytic method with a cross-sectional approach, data from 84 patients, aged 15-70, were collected between May and October 2023. Predominant side effects included edema (38.10%), dizziness (28.57%), fatigue (17.85%), and nausea (15.48%). Findings indicated age (p=0.013) and Amlodipine dosage (p=0.002) correlated with side effect risks. However, administration method analysis was hindered by consistent post-meal consumption in all participants. In conclusion, this research underscores the relevance of age and Amlodipine dosage in side effect risks for hypertensive patients. Practical implications include refined medication management strategies to improve overall patient well-being.